REDD: The Copenhagen Effect - Feja Lesniewska (Law, Environment and Development Journal, 2010)
An agreement on reducing emissions from avoided deforestation and degradation at the UNFCCC Conference of the Parties 15 (COP 15) in Copenhagen December 2010 was not forthcoming. For a number of reasons this is a welcome outcome as several important outstanding legal and technical issues remain unresolved. This article examines the results from COP 15 including the Copenhagen Accord. It focuses on the key issues of principles, finance models, and environmental and social safeguards. It concludes with an assessment of the potential effect that the COP 15 will have on REDD negotiations this coming year prior to the UNFCCC COP 16 in Mexico December 2010.